Magnetic Anisotropy of Cyanide‐Bridged Core and Core–Shell Coordination Nanoparticles Probed by X‐ray Magnetic Circular Dichroism. Issue 21 (20th March 2013) - Prado, Yoann; Arrio, Marie‐Anne; Volatron, Florence; Otero, Edwige; Cartier dit Moulin, Christophe; Sainctavit, Philippe; Catala, Laure; Mallah, Talal
Abstract The local symmetry and local magnetic properties of 6 nm‐sized, bimetallic, cyanide‐bridged CsNiCr(CN)6 coordination nanoparticles 1 and 8 nm‐sized, trimetallic, CsNiCr(CN)6@CsCoCr(CN)6 core–shell nanoparticles 2 were studied by X‐ray absorption spectroscopy (XAS) and X‐ray magnetic circular dichroism (XMCD). The measurements were performed at the NiII, CoII, and CrIII L2, 3 edges. This study revealed the presence of distorted NiII sites located on the particle surface of 1 that account for the uniaxial magnetic anisotropy observed by SQUID measurements. For the core–shell particles, a combination of the exchange anisotropy between the core and the shell and the pronounced anisotropy of the CoII ions is the origin of the large increase in coercive field from 120 to 890 Oe on going from 1 to 2. In addition, XMCD allows the relative orientation of the magnetic moments throughout the core–shell particles to be determined. While for the bimetallic particles of 1, alignment of the magnetic moments of CrIII ions with those of NiII ions leads to uniform magnetization, in the core–shell particles 2 the magnetic moments of the isotropic CrIII follow those of CoII ions in the shell and those of NiII ions in the core, and this leads to nonuniform magnetization in the whole nanoobject, mainly due to the large difference in local anisotropy between the CoII ions belonging to the surface and the NiII ions in the core.